El juego de roles en el desarrollo de la psicomotricidad en niños y niñas de 4 a 5 años de edad de la Unidad Educativa Verbo Divino del cantón Guaranda, provincia Bolívar, periodo 2024 - Córdova Calderón, María Angela (2024)
The present investigation entitled “IMPACT OF ROLE-PLAYING IN THE DEVELOPMENT OF PSYCHOMOTOR SKILLS IN CHILDREN FROM 4 TO 5 YEARS OF AGE OF THE EDUCATIONAL UNIT GUARANDA, BOLIVAR PROVINCE, PERIOD 2024” had as general objective to determine the impact of role-playing in the development of psychomotor skills in children from 4 to 5 years of age, the research has a qualitative and quantitative approach, which allowed us to collect information for our project and then we came to analyze and interpret it. Something highly fundamental was the application of the surveys to the teachers to know their point of view and with them also an application of an observation form which allowed us to deeply analyze the children to know their abilities and skills, Activities that helped to develop psychomotor skills in children were also carried out, which also facilitated the use of these activities by teachers and their integration into their planning. Finally, a role-playing guide was proposed so that children can develop their psychomotor skills in the classroom, because only through the movements and learning acquired during the game, children strengthen their physical abilities and improve their intelligence. For several reasons, role-playing should be recognized as a powerful educational tool for the integral development of children